Effects of different estrus synchronization and superovulation treatments on ovarian response and embryo collection in the South African Boer goat - Mpoyo, Robert Kabyla (Stellenbosch : Stellenbosch University, 2012)
Thesis (MSc)--Stellenbosch University, 2004.